Karawitan Musical Work Surya Kala | Karya Musik Karawitan Surya Kala - Mahesa, Dewa (GHURNITA: Jurnal Seni Karawitan, 2024)
The solar system is a collection of celestial bodies consiting of the sun and all the objects that revolve around it, inclouding the eight known planets with elliptical orbits. The aim of creating the musical piece “Surya Kala” is to find out the process of creating this work, to know the musical elements contained in this work and to know the structure of the musical piece “Surya Kala”. In creating the musical “Surya Kala” the stylist based on I Wayan Dibia’s art creation process which consists of five stage, namely the conception stage (ngarencana), exploration stage (ngewacak), inspiration stage (ngawirasa), execution stage (ngewangun), ngebah/maedeng (Dibia, 2020:33). “Surya Kala” takes the form of musical music which moves from the cycle of sunrise to sunset by creating a new atmosphere which will be expressed in the Semarandhana Gamelan media owned the Çudamani Art Studio, but in this case the creator only processed the gamelan instruments because in this work doesn’t require vocal training. The reason creator used Gamelan Semarandhana was so that the creator could get a wider range of tones in carrying out the exploration process in this work. The musical piece “Surya Kala” will use a division system which will represent each phase of the sun which is divided into three, namely part one ehich depicts the atmosphere of the rising sun. These three parts will be arranged in such a way that each part has its own character to suit the ideas and atmosphere interpreted by the creator.